First-principles LCAO study of the low and room temperature phases of CdPS3 - Kuzmin, Alexei (AIP Publishing, 2020)
The electronic and atomic structure of a bulk 2D layered van-der-Waals compound CdPS3 was studied in the low (R3) and room (C2/m) temperature phases using first-principles calculations within the periodic linear combination of atomic orbitals method with hybrid meta exchange-correlation M06 functional. The calculation results reproduce well the experimental crystallographic parameters. The value of the indirect band gap Eg = 3.4 eV for the room-temperature monoclinic C2/m phase is close to the experimental one, while the indirect band gap Eg = 3.3 eV was predicted for the low-temperature trigonal R3 phase. The effect of hydrostatic pressure on the band gap in both phases was studied in the pressure range from 0 to 40 GPa. In both cases, the pressure dependence of the band gap passes through a maximum, but at different pressures. In the R3 phase, the band gap reaches its maximum value of ~4 eV at ~30 GPa, whereas in the C2/m phase, the maximum value of ~3.6 eV is reached already at ~8 GPa.
A.K. is grateful to the Latvian Council of Science project no. lzp-2018/2-0353 for ﬁnancial support. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; CdPS3; layered compound; electronic structure; ﬁrst principles calculations; high pressure